Caracterização morfológica, agronômica e análise multivariada de genótipos de feijão-caupi - MEDEIROS, Jamile Erica de (2018)
Cowpea bean is a legume belonging to the Fabaceae family, with an annual cycle, presenting a certain rusticity and being widely cultivated in Brazil due to its good adaptation to the climate of the country. It has a wide genetic variability and because of its great consumption in the country, studies involving the characterization and improvement of the crop has been growing over time. With this, the objective of the present work was to characterize different genotypes of the cowpea bean by means of morphological and agronomic descriptors, and to evaluate the genetic divergence between them. For this, 12 genotypes of cowpea bean were used: Belém do São Francisco 2, BRS Cauamé, Cavaleiro 8, Encruzilhada 1, Juazeiro 7, Macaibo, Manteiguinha Santarém, Pingo de Ouro, Portalegre 2, Sempre Verde, Tucuruí 1 and Vitória 2, provided by the Agronomic Institute of Pernambuco (IPA). The experiments were conducted in field, at the Experimental Station of the Agronomic Institute of Pernambuco (IPA), located in the city of Itapirema-PE, and in laboratory, at the Seeds Laboratory of the Agronomy Department of the Federal Rural University of Pernambuco (UFRPE), at the headquarters, in 2016 and 2017. In the field experiment, the morphological and agronomic characterization of the 12 genotypes of cowpea bean were carried out, in which the qualitative and quantitative characteristics of some leaf, plant, inflorescence and pod characteristics were evaluated, measured and recorded, according to the specific descriptors for cowpea bean, with some adaptations. The morphological aspects of seeds and germination, characterization of seedlings, as well as the evaluation of germinative characters were carried out in laboratory. For the field experiment, a randomized complete block design was used, with 12 treatments (genotypes) in four replicates, and the experimental plot consisting of four lines of three meters of length each, using the spacing 0,50m x 0,25m and the distance of 2m between blocks. For the experiment in laboratory, the design was completely randomized, with 12 treatments (genotypes) and four replicates of 25 seeds each. The comparison of means was made by the Tukey test at 5% of probability, and the multivariate analysis was performed using the genetic divergence analysis of the genotypes, the dissimilarity measure by the Generalized Distance of Mahalanobis (D²), by the Genes statistical program. There is genetic divergence among the genotypes, with biometric, morphological and agronomic variations among them, being the quantitative characteristics the ones that contributed most to the diversity verification among the materials. From the Generalized Distance of Mahalanobis (D2), three distinct groups were formed, being this information important for the identification of the most divergent materials, and it can be used to improve the breeding crop, as well as for complementary information useful to germplasm banks. There was influence of the genetic components in the phenotypic manifestation of the agronomic and production characteristics evaluated in the genotypes of cowpea bean. Regarding the germinative and vigor parameters, the genotypes of Belém do São Francisco, BRS Cauamé, Cavaleiro 8, Sempre Verde e Macaibo were the most important. Considering morphological aspects of germination, the Macaibo genotype was differentiated from the others by the presence of trichomes on the prothrophic margin.